PENINGKATAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA SISWA MELALUI MODEL AUDITORY INTELLECTUALLY REPETITION (AIR) DI SMP NEGERI 5 TAKENGON - Leni Agustina Daulay (Program Studi Pendidikan Matematika, Fakultas Keguruan Dan Ilmu Pendidikan, Universitas Alwashliyah Medan, 2023)
The purpose of this study was to see an increase in students’ mathematical problem solving skills using Auditory Intellectually Repetition (AIR) learning model on straight line equation in class VIII SMP Negeri 5 Takengon. This study used a quantitative approach with a quasi-experimental type of research, class VIII1 as the experimental class uses the Auditory Intellectually Repetition (AIR) learning model and VIII2 as the control class uses the direct learning model. The data analysis used by the data manager in this study was t-test and the N-gain test was used to see the increase. Based on the results of hypothesis testing ttest > ttable or 2,268 > 2,042 thus Ha is accepted. The results of the research n-gain test can be concluded 0,30 ? g ? 0,70 that the is an increase in student’s mathematical problem solving abilities towards Auditory Intellectually Repetition (AIR) learning model. The conclusion is that by using Auditory Intellectually Repetition (AIR) learning model in class VIII SMP Negeri 5 Takengon, students are more active because they are directly involved in being able to determine the material being studied and relate it to real life situations.